( al-Raj‘ah in Imami Doctrine: A Study on Its Reality, Possibility, and Occurrence from the Perspective of the Qur’an and the Narrations According to Imami Shi‘a Scholars) - Muslim Daoud , Haider ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
This research aims to clarify and affirm the reality of Rajʿa (return to life) in Islamic belief, particularly from the perspective of Twelver Shia theology, through evidence drawn from the Qur’anic texts and narrations (hadiths). Rajʿa is an Islamic concept that refers to the return of certain deceased individuals to worldly life before the Day of Judgment. It is closely linked to the appearance of Imam al-Mahdi (may Allah hasten his reappearance) and signifies God’s act of bringing some of the dead back to life so that He may honor a group and humiliate another, distinguishing between the truthful and the false. This is based on Qur’anic evidence, prophetic traditions, and rational arguments. Belief in God’s power to resurrect the dead is an essential part of belief in the Hereafter, which is one of the core pillars of Islamic creed. Both textual and rational proofs confirm the possibility of Rajʿa. The Qur’an contains references to resurrection in this world, such as the stories of the Israelites and ʿUzayr (or Jeremiah), indicating its occurrence. Likewise, various narrations and historical reports mention that Rajʿa happened among past nations, further supporting its potential future occurrence. From a rational standpoint, Rajʿa poses no impossibility; it resembles bodily resurrection and return but occurs in this world prior to the Final Day. This is supported by God’s absolute power to resurrect the dead, as affirmed in both the Qur’an and the Sunnah. Shia scholars have cited Qur’anic verses and prophetic narrations as evidence for the possibility of Rajʿa, affirming that resurrecting the dead is both theologically and rationally plausible. DOI: https://doi.org/10.54633/2333-024-057-017